PROBLEMATIKA DAN SOLUSI PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM - Rusiadi Rusiadi (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
History learning applies deep attention, because the current history learning has problems and requires solutions to be taught in schools. The importance of learning history is because, history is a phenomenological description of events that can be used as lessons for general and specific knowledge, in recognizing the existence of an event. Psychological and methodological factors are a problem that must be considered in teaching history. The expected solution is to understand the importance of studying history and understanding the nature of historical reduction and reinterpretation as well as understanding the teaching approach